Attenuation of TCR-induced transcription by Bach2 controls regulatory T cell differentiation and homeostasis - Sidwell, Tom (Nat Commun, 2020)
Differentiation and homeostasis of Foxp3(+) regulatory T (Treg) cells are strictly controlled by T-cell receptor (TCR) signals; however, molecular mechanisms that govern these processes are incompletely understood. Here we show that Bach2 is an important regulator of Treg cell differentiation and homeostasis downstream of TCR signaling. Bach2 prevents premature differentiation of fully suppressive effector Treg (eTreg) cells, limits IL-10 production and is required for the development of peripherally induced Treg (pTreg) cells in the gastrointestinal tract. Bach2 attenuates TCR signaling-induced IRF4-dependent Treg cell differentiation. Deletion of IRF4 promotes inducible Treg cell differentiation and rescues pTreg cell differentiation in the absence of Bach2. In turn, loss of Bach2 normalizes eTreg cell differentiation of IRF4-deficient Treg cells. Mechanistically, Bach2 counteracts the DNA-binding activity of IRF4 and limits chromatin accessibility, thereby attenuating IRF4-dependent transcription. Thus, Bach2 balances TCR signaling induced transcriptional activity of IRF4 to maintain homeostasis of thymically-derived and peripherally-derived Treg cells.